2019
DOI: 10.1007/s10479-019-03304-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts on efficiency of merging the Swedish district courts

Abstract: Judicial courts form a stringent example of public services using partially sticky inputs and outputs with heterogeneous quality. Notwithstanding, governments internationally are striving to improve the efficiency of and diminish the budget spent on court systems. Frontier methods such as data envelopment analysis are sometimes used in investigations of structural changes in the form of mergers. This essay reviews the methods used to evaluate the ex post efficiency of horizontal mergers. Identification of impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The current literature suggests that judicial efficiency has a positive impact on economic growth (Chemin, 2009), influencing both firm dynamics (e.g., Johnson et al, 2002;Dougherty, 2014;Lichand & Soares, 2014;Falavigna et al, 2019) and the financial markets (e.g., Djankov et al, 2008;Qian & Strahan, 2007;Ponticelli & Alencar, 2016). Consequently, there is a great need to improve the supply of justice, by correctly assessing the performance of the courts and of the judicial system as a whole (e.g., Silva, 2018;Mattsson & Tidanå, 2019;Agrell et al, 2020;Ippoliti & Tria, 2020).…”
Section: Theoretical Background: Judicial Efficiency and Company Dynamentioning
confidence: 99%
“…The current literature suggests that judicial efficiency has a positive impact on economic growth (Chemin, 2009), influencing both firm dynamics (e.g., Johnson et al, 2002;Dougherty, 2014;Lichand & Soares, 2014;Falavigna et al, 2019) and the financial markets (e.g., Djankov et al, 2008;Qian & Strahan, 2007;Ponticelli & Alencar, 2016). Consequently, there is a great need to improve the supply of justice, by correctly assessing the performance of the courts and of the judicial system as a whole (e.g., Silva, 2018;Mattsson & Tidanå, 2019;Agrell et al, 2020;Ippoliti & Tria, 2020).…”
Section: Theoretical Background: Judicial Efficiency and Company Dynamentioning
confidence: 99%
“…We now illustrate the introduced PCU measures on an unbalanced sample of Swedish district courts used in Agrell, Mattsson, and Månsson (2020) and Mattsson and Tidanå (2019) 1 . From the initial data set containing yearly data related to 102 courts in the period 2000-2017, all available records are selected: this results in 1836 observations.…”
Section: Sample Data: Descriptive Statisticsmentioning
confidence: 99%
“…Following Agrell, Mattsson, and Månsson (2020) and Mattsson and Tidanå (2019), the production of Swedish district courts is specified as generating three outputs ((i) criminal cases, (ii) civil cases, and (iii) petitionary matters) from four inputs ((i) judges, (ii) law clerks, (iii) other personnel, and (iv) court area). Agrell, Mattsson, and Månsson (2020, p. 662) discuss how these three output categories are generated using an aggregation procedure for self-reported time consumption starting with fourteen output categories.…”
Section: Sample Data: Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, employing SFA, Antonucci et al ( 2014 ) showed that the efficiency of courts in Italy depends upon the vacancies and per capita expenditure. Moreover, considering the legislative reforms, a study in the context of Sweden by Agrell et al ( 2020 ) provided evidence of how merging the district courts, on average, made the whole sector more efficient. The impact of judiciary on the firm in Indian context was probed by Chakraborty ( 2016 ) which reported how the judicial quality is a significant factor in determining firm’s performance (especially for contract-intensive) both international and domestic.…”
Section: Literature Reviewmentioning
confidence: 99%